2012
DOI: 10.1136/annrheumdis-2011-201176
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of coronary heart disease and cardiovascular risk factors in a national cross-sectional cohort study of systemic sclerosis

Abstract: This is the first report of an increased prevalence of CHD in SSc patients. Further studies are required to determine the relative contribution of scleroderma-specific factors such as microvascular disease to the development of CHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
73
4
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 24 publications
(23 reference statements)
7
73
4
4
Order By: Relevance
“…It is unlikely that traditional CV risk factors per se fully explain the increased prevalence of atherosclerosis in SSc, as after adjustment of confounding factors in HS and SSc patients the risk of subclinical atherosclerosis was still 3 times higher than HS. Studies of atherosclerosis and CVD in SSc, including large population-based studies, also did not suggest strong contributions of traditional CV risks on either atherosclerosis or CVD (3,4,17,38). In our study, despite the higher CRP levels, longer disease duration, and worse CV risk profile with higher systolic and diastolic BP, waist circumference, and total cholesterol levels in RA patients, the frequency of subclinical atherosclerosis in SSc patients was similar to RA patients.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…It is unlikely that traditional CV risk factors per se fully explain the increased prevalence of atherosclerosis in SSc, as after adjustment of confounding factors in HS and SSc patients the risk of subclinical atherosclerosis was still 3 times higher than HS. Studies of atherosclerosis and CVD in SSc, including large population-based studies, also did not suggest strong contributions of traditional CV risks on either atherosclerosis or CVD (3,4,17,38). In our study, despite the higher CRP levels, longer disease duration, and worse CV risk profile with higher systolic and diastolic BP, waist circumference, and total cholesterol levels in RA patients, the frequency of subclinical atherosclerosis in SSc patients was similar to RA patients.…”
Section: Discussioncontrasting
confidence: 63%
“…Although increased CVD in SSc has been reported in population-based cohort studies (2)(3)(4)36), there are controversial data regarding the prevalence of atherosclerosis in SSc (9-11,13-18,37). The present study showed that SSc patients had significantly higher cIMT and more frequent carotid plaques and increased cIMT, i.e., subclinical atherosclerosis, compared to HS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, a recent, large cross-sectional study conducted by Ngian et al. [24] showed that the prevalence of coronary heart disease in SSc patients was three times higher than that of healthy subjects. In addition, Man et al [25] suggested that SSc is related to an increased risk of myocardial infarction (MI), stroke, and peripheral vascular diseases in their population-based study.…”
Section: Discussionmentioning
confidence: 99%
“…[13,29,30] Considering that the participants in our study were rather asymptomatic, evaluating the CACS in these subjects may not have been appropriate. However, because SSc has been considered to be a risk factor for cardiovascular disease in previous studies, [24,25] measuring the CACS via MDCT in SSc patients may provide valuable information regarding the assessment and prediction of coronary heart disease. In addition, we conjecture that CACS evaluated by MDCT could be applied as a gatekeeper in the workup of SSc patients suspected of having cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%